Experimental evidence of the role of quasilocalized phonons in the thermal conductivity of simple alcohols in orientationally ordered crystalline phases - Krivchikov, A.I.; Bermejo, F.J.; Sharapova, I.V.; Korolyuk, O.A.; Romantsova, O.O. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The thermal conductivity к(T) of crystalline alcohols (methyl, ethyl and 1-propyl) within their thermodynamic equilibrium phases for T ≥ 2 K and under the equilibrium vapor pressures has been measured and analyzed. While such compounds usually exhibit a rich polymorphism including amorphous and partially ordered crystals, the phases here explored correspond to crystals showing complete orientational order. The results show that the temperature dependence of к(T) above its maximum deviates from the expected decrease following a 1/T law with increasing temperature arising from anharmonic interactions involving acoustic excitations. Such a deviation is here attributed to the presence of a component кII(T) corresponding to the shortest-lifetime phonons (Cahill–Pohl model) additional to that кI(T) related to propagating phonons and thus: к(T) = кI(T) + кII(T). Above T = 40 K кI(T) does follow the law 1/T and кII(T) is basically temperature independent. The component кI(T) is well described by the Debye–Peierls model taking into account the phonon–phonon Umklapp processes and phonon scattering by dislocations. In turn, the contribution кII(T) isattributed to the effects of higher lying excitations which get thermally populated above some 40 K. Finally, a systematic trend is found concerning the strength of phonon–phonon scattering which is seen to diminish as the number of carbon atoms in the alcohol molecule increases.